The Effect of Profitability, Liquidity, Profit Growth, and Leverage on Earning Quality (Empirical Study of Manufacturing Companies Listed on IDX Period 2017 - 2020) - Syaharani Ain Tsabit; Eko Wahjudi (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
This research aims to analyze the effect of profitability, liquidity, profit growth, and Leverage on earning quality. The object of research is a manufacturing company that has been listed on the Indonesia Stock Exchange for the period 2017 to 2020. The amount of population is 118 companies. The method of selecting samples is purposive sampling, thus the number of samples was found is 93 samples. Data analysis techniques use multiple linear regression analysis techniques with SPSS 25 software. The analysis used in this research uses multiple linear regression analysis techniques with SPSS 25 software. The author gets five points of conclusion: 1) profitability can affect earning quality; 2) liquidity does not affect earning quality; 3) profit growth can affect earning quality, 4) leverage does not affect earning quality; 5) profitability, liquidity, profit growth, and leverage simultaneously affect towards earning quality.